How Do EFL Students Across Gender Perceive Classpoint toward Their Motivation in Learning English? - Ramadhani, Frenni Shalsabillah; Unsiah, Frida (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2024)
This study seeks the difference between female and male students' intrinsic and extrinsic motivation and attitudes toward using Classpoint in EFL learning. Applying quantitative research, 61 EFL high school students of Brawijaya Smart School participated in this research. The instrument used in this study was a questionnaire consisting of 21 items using a Likert-type scale—the chosen items comprised three topics (students' intrinsic and extrinsic motivation and attitudes toward the use of Classpoint). The data analysis uses SPSS 27 and t-test to seek the significance of the result of the present study. This research indicates that female students have a higher motivation rate and attitude toward using Classpoint in EFL classrooms and that students across genders significantly differ in their perception of intrinsic motivation and attitudes. It also showed that utilizing Classpoint augments intrinsic motivation better than extrinsic motivation. The result implies English teachers should motivate and encourage male students to participate in the learning process by providing fun activities and giving rewards.